ALT+F: APLIKASI PENCARIAN LAWAN TANDING FUTSAL BERBASIS MOBILE ANDROID - Muhaqiqin Muhaqiqin; Rikendry Rikendry (J-Icon : Jurnal Komputer dan Informatika, 2021)
Futsal is a sport that is currently popular in Indonesia, including in the city of Bandar Lampung which has quite a lot of fans of this futsal sport. One thing that makes this sport very popular is that in futsal, each team can compete with other teams. However, to be able to compete with other teams, sometimes each team has to wait for a futsal competition or tournament. Meanwhile, for playing matches with other teams when there is no competition, each team finds it difficult to find other teams that are willing to compete as a step to train in preparing the team for competitions or tournaments. The purpose of this study was to build an Android mobile based Futsal Match Training Application (ALT + F) to make it easier for every futsal team in Bandar Lampung to find sparring opponents. The software as a service methodology is used as the basis for the stages to build this application. Based on the results of testing using blackbox testing, the function of each feature developed in the ALT + F application is 100% functioning, so that the ALT + F application can find sparring opponents for the futsal team in Bandar Lampung.